AI Automation with Anthropic Claude API's Agentic Computer Use. - Villalobos, Ray (linkedin.com, 2024)
Understand the risks and rewards of working with Claude’s computer use desktop automation. Use AI-driven clicks, typing, and workflow control features with an eye on safety and security.